The Effect Of Service Quality And Promotion On Customer Satisfaction At The Revolving Fund Management Institution Of Micro, Small And Medium Enterprise Cooperatives Head Office In South Jakarta - Anggraini, Nina; Hartuti, Elizabeth Tika Kristina (Management Science Doctoral Program, Pasundan University, 2024)
This study aims to determine the effect of service quality and promotion on customer satisfaction at the Revolving Fund Management Institution of Micro, Small and Medium Enterprises Cooperatives Head Office in South Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study show that service quality has a significant effect on customer satisfaction of 43.9%, the hypothesis test obtained t count> t table or (5.784> 1.652). Promotion has a significant effect on customer satisfaction of 43.8%, the hypothesis test obtained t count> t table or (5.756> 1.652). Service quality and promotion simultaneously have a significant effect on customer satisfaction with the regression equation Y = 4.939 + 0.340X1 + 0.419X2 and a contribution of 58.2%, the hypothesis test obtained F count> F table or (67.545> 3.04).